2015
DOI: 10.1210/jc.2015-2372
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Cancer Among Acromegaly Patients: Results From the German Acromegaly Registry

Abstract: Cancer screening strategies need to take incidence into account, which does not seem to be substantially higher in treated acromegaly patients than in the general population for any site of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 36 publications
3
49
1
5
Order By: Relevance
“…Standardized incidence ratio (SIR) was available from 11 series, and in three of them, cancer incidence was not increased (12,18,28). In five series, the estimated overall SIR for malignancies was increased by a magnitude of 1.5-to 3.4-fold (15,16,19,21,23), whereas in two studies, increased risk was only observed for women (13) and in one only for men (20) (Table 1).…”
Section: Incidence/prevalencementioning
confidence: 99%
See 3 more Smart Citations
“…Standardized incidence ratio (SIR) was available from 11 series, and in three of them, cancer incidence was not increased (12,18,28). In five series, the estimated overall SIR for malignancies was increased by a magnitude of 1.5-to 3.4-fold (15,16,19,21,23), whereas in two studies, increased risk was only observed for women (13) and in one only for men (20) (Table 1).…”
Section: Incidence/prevalencementioning
confidence: 99%
“…A review of 17 series published between 1957 and 2015, where overall cancer incidence in acromegaly was investigated, revealed 7723 patients with 708 cases of cancer, resulting in a mean cancer incidence of 10.8%, with percentages varying from 4.8 to 21.3% (12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28). Standardized incidence ratio (SIR) was available from 11 series, and in three of them, cancer incidence was not increased (12,18,28).…”
Section: Incidence/prevalencementioning
confidence: 99%
See 2 more Smart Citations
“…Routine thyroid ultrasound (US) screening has been suggested in a recent meta-analysis (Wolinski et al 2014), and in a large, cross-sectional study with extensive US and fine-needle aspiration analyses (Reverter et al 2014). However, in a recent study, Petroff and coworkers reported, by analysing a cohort of 446 German patients with acromegaly, that cancer incidence is not increased in treated patients with acromegaly when compared with the general population, not for any type of cancer studied (Petroff et al 2015). In line with this, in the present study, 31 patients (27%) died of cancer, with an identical cancer death rate of 27% in the large general population during 20 years of follow-up.…”
Section: :6mentioning
confidence: 99%